Public health facility resource availability and provider adherence to first antenatal guidelines in a low resource setting in Accra, Ghana. Issue 1 (December 2016) - Amoakoh-Coleman, Mary; Agyepong, Irene; Kayode, Gbenga; Grobbee, Diederick; Klipstein-Grobusch, Kerstin; Ansah, Evelyn
Abstract Background Lack of resources has been identified as a reason for non-adherence to clinical guidelines. Our aim was to describe public health facility resource availability in relation to provider adherence to first antenatal visit guidelines. Methods A cross-sectional analysis of the baseline data of a prospective cohort study on adherence to first antenatal care visit guidelines was carried out in 11 facilities in the Greater Accra Region of Ghana. Provider adherence was studied in relation to health facility resource availability such as antenatal workload for clinical staffs, routine antenatal drugs, laboratory testing, protocols, ambulance and equipment. Results Eleven facilities comprising 6 hospitals (54.5 %), 4 polyclinics (36.4 %) and 1 health center were randomly sampled. Complete provider adherence to first antenatal guidelines for all the 946 participants was 48.1 % (95 % CI: 41.8–54.2 %), varying significantly amongst the types of facilities, with highest rate in the polyclinics. Average antenatal workload per month per clinical staff member was higher in polyclinics compared to the hospitals. All facility laboratories were able to conduct routine antenatal tests. Most routine antenatal drugs were available in all facilities except magnesium sulphate and sulphadoxine-pyrimethamine which were lacking in some. Antenatal service protocols and equipment were also available in all facilities. Conclusion Although antenatal workload varies across different facility types in the Greater Accra region, other health facility resources that support implementation of first antenatal care guidelines are equally available in all the facilities. These factors therefore do not adequately account for the low and varying proportions of complete adherence to guidelines across facility types. Providers should be continually engaged for a better understanding of the barriers to their adherence to these guidelines.